Evaluating the Implementation of a Multi‐Component Intervention to Prevent Surgical Site Infection and Promote Evidence‐Based Practice. Issue 3 (13th April 2020) - Lin, Frances; Marshall, Andrea P.; Gillespie, Brigid; Li, Yu; O'Callaghan, Frances; Morrissey, Shirley; Whitelock, Karen; Morley, Nicola; Chaboyer, Wendy
Abstract: Background: Published clinical practice guidelines on surgical site infection prevention are available; however, adherence to these guidelines remains suboptimal. Aims: The aim of this study was to evaluate the effectiveness and perceived benefits of intervention and implementation strategies co‐created by researchers and clinicians to prevent surgical site infections. Methods: This mixed‐method evaluation study involved an audit of nurses' wound care practices, followed by focus group and individual interviews to understand the perceived benefits of the intervention and implementation strategies. Descriptive statistical analyses were used to compare post‐intervention audit data with baseline results. Deductive and inductive content analyses were undertaken on the qualitative data. Results: The audit showed improvements in using aseptic technique and wound care documentation practices following intervention implementation. Nurses perceived the change champion as effective in role‐modelling good practice. Education strategies including a poster and using a scenario‐based quiz were viewed as easy to understand and helpful for nurses to apply aseptic technique in practice. The instructions and education conducted to improve documentation were considered important in the success of the Wound Care Template implementation. Linking Evidence to Action: The integrated knowledge translation approach used in this study ensured the intervention and the implementation strategies employed were appropriate and meaningful for clinicians. Such strategies may be used in other intervention studies. The change champion played an important role in driving change and acted as a vital partner during the co‐creation and the implementation processes. Ongoing education, audit and feedback became integrated in the ward nurses' routine practice, which has the potential to continuously improve and sustain evidence‐based practice.